Tunisia : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report, 2008)
This 2008 Article IV Consultation highlights that Tunisia's sound economic policies and pragmatic approach to structural reforms continue to bear fruit, as evidenced by strong growth and improved social indicators. Real GDP growth averaged 5 percent a year while the macroeconomic and financial position strengthened substantially during the past decade. The short-term outlook is encouraging despite the challenging international environment. The fiscal deficit is projected to remain at 3 percent of GDP. The medium-term outlook remains favorable with growth projected at above 6 percent sustained by strong foreign direct investment.